Peningkatan Minat Pembayaran Zakat UMKM Coffee Shop di Tasikmalaya - Arief Budiman; Azizah Fauziyah; Nizza Nadya Rachmani (Universitas Pendidikan Indonesia, 2022)
AbstractZakat is a tool that can be used to overcome the problem of poverty. The potential contribution of zakat in Indonesia is estimated to reach 271 trillion rupiah. However, the potential of zakat is not yet as expected, which is only 1.3 percent of it or about 3.7 trillion rupiah. This happens because one of the lack of individual interest to pay zakat through the Organization of Zakat Management (OZM). This study aims to analyze the theory of planned behavior on increasing the intention of an individual to paying zakat through the organization of zakat management. This research uses quantitative method with multiple linear regression data analysis. The number of samples in this study amounted to 72 respondents who are SMEs Coffee Shop. The research has shown that the theory of planned behavior can give influence on increasing the intention of lecturers of the Faculty of Economics and Business Education Indonesia University of Education to pay zakat through the organization of zakat management. This result is in accordance with the theory that theory of planned behavior can give influence on increasing the intention of muzakki to pay zakat Kata Kunci: Intention to pay zakat, theory of planned behavior, zakat, organization of zakat management, intention AbstrakZakat merupakan suatu alat yang dapat digunakan untuk mengatasi masalah kemiskinan. Potensi kontribusi zakat di Indonesia diperkirakan dapat mencapai 271 triliun rupiah. Walaupun begitu, potensi zakat yang didapatkan belum sesuai perkiraan, yaitu hanya mencapai 1,3 persennya saja atau sekitar 3,7 triliun rupiah. Hal tersebut terjadi salah satu disebabkan kurangnya minat individu untuk membayarkan zakatnya melalui Organisasi Pengelola Zakat (OPZ). Penelitian ini bertujuan untuk menganalisis theory of planned behavior dalam meningkatkan minat seorang individu dalam membayarkan zakatnya melalui organisasi pengelola zakat. Penelitian ini menggunakan metode kuantitatif dengan teknik analisis data regresi linear berganda. Jumlah sampel dalam penelitian ini berjumlah 72 responden yang merupakan UMKM Kafe Kopi. Dari hasil penelitian yang dilakukan diketahui bahwa theory of planned behavior dapat memberikan pengaruh dalam meningkatkan minat pengusaha UMKM Kafe Kopi untuk membayar zakat melalui organisasi pengelola zakat. Hal tersebut sesuai dengan teori bahwa theory of planned behavior dapat memengaruhi minat seorang muzakki untuk membayar zakat. Kata Kunci: Minat membayar zakat, theory of planned behavior, zakat, organisasi pengelola zakat, minat